Hambatan Sertifikasi Halal pada UMKM di Makassar: Perspektif Finansial, Digital, dan Tata Kelola - Reslawati Reslawati; R. Adang Nofandi; Ahsanul Khalikin (Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study examines how the dynamics of halal certification shape the experiences of micro, small, and medium enterprises (MSMEs) in Makassar, South Sulawesi, in the aftermath of the Halal Product Assurance Law (UU JPH). While previous scholarship has repeatedly highlighted financial burdens, regulatory complexity, and technological gaps, few studies explore how these challenges unfold in specific local contexts. Drawing on a qualitative design that combined field observation, document analysis, and semi-structured interviews, this research identifies the barriers encountered by MSMEs and evaluates the real outcomes of government-led support initiatives in Makassar. The findings reveal that persistent financial constraints, uneven levels of digital literacy, and weak institutional coordination remain the most significant obstacles to effective certification. These issues are analyzed through the lenses of policy implementation, governance, and service quality, showing that systemic institutional weaknesses, rather than mere technical inefficiencies, lie at the heart of these challenges. By situating Makassar’s case within broader debates on Indonesia’s halal governance, the study demonstrates how localized insights can illuminate gaps in national implementation frameworks. The results underscore the urgent need for targeted financial assistance, integrated governance reforms, and sustained capacity-building programs to ensure that MSMEs are not only able to comply with certification requirements but also benefit from their participation in the growing halal economy, while providing context sensitive field perspectives that are rarely addressed in existing literature.